Acción de Protección para la Reparación de los Derechos de las Personas en Condición de Doble Vulnerabilidad - Barreto Morales., Ana Cristina (2017)
For the development of this thesis I found relevant conduct a study on protective action for repairing the rights of people living in double vulnerability because as there is a secondary standard to ensure the protection of their rights they are subject of violation of constitutional rights such as rights to health, life and decent housing. For this reason it is necessary to make the respective investigation into the issues raised in order to make a theoretical, normative study Protective action to repair the rights of people who are in a situation of dual vulnerability as having no definition of double vulnerability these people are victims of discrimination. To further create legal reforms that can be implemented within our rules in this way more guarantees are given to these people and that within our rules are an extension of the protective action to ensure the protection of the rights that are enshrined within our Constitution. The methods that have been used for this research work have been vital mainly the documentary method that allowed us to collect the information necessary for the foundation and development of the subject under investigation and the inductive method was used in the approach surveys the same that were made to professional rights and experts on the subject, who through the answers given in each of the questions they were able to state that whether to make an extension of the protective action to ensure a comprehensive repair rights to these people who are in condition of double vulnerability.